Determinan Kecemasan Ibu Hamil dalam Menerima Vaksin Covid-19 Di Puskesmas Nanga Pinoh: Determinants the Anxiety of Pregnant Mothers in Receiving the Covid-19 Vaccine in Puskesmas Nanga Pinoh - Rosalina Noberta; Juda Julia Kristiarini; Siswanto Pabidang (Journal of Health, 2023)
Background: Death from Covid-19 priority issue times. Governments issued regulations vaccination. Pregnant women one the vulnerable groups to transmission Covid-19, infection pregnant women results death, premature birth, postpartum hemorrhage and complications. Objective: Analyze effect of determinants economic status, level knowledge and information health workers the anxiety pregnant women receiving Covid-19 vaccine Nanga Pinoh Health Center. Methods: Study used design (cross-sectional), quantitative correlation method measuring economic status, level of knowledge and information health workers on pregnant women's anxiety in receiving Covid-19 vaccine. The research sample used total sampling, namely 100 mothers gestational age 12 weeks - 32, 6 days the Nanga Pinoh Health Center, Melawi Regency, West Kalimantan 2022. Data collection used questionnaires and interviews. Analysis, univariate test, Bivariate and Multivariate. Results: Univariate test the characteristics respondents Age > 35 years (50%), < 20 years. Higher education (33%, no school - junior high school (22%). Employment IRT (40%), Farmer etc. (14%). Trimester 2 (72%), Trimester I (28%). Research variables Economic status KS 2 - KS 3 ++ (87%), family PS –KS 1 (13%) Level of understanding-application knowledge (62%), know (38%) Direct information (73%), not direct (27%) Mild-moderate anxiety (69%), severe panic (31%) Bivariate analysis economic status - anxiety (p value = 0.02 ), knowledge - anxiety (p value = 0.00), information - anxiety (p value = 0.05) Conclusion: The results  study concluded that economic status, level knowledge and information health workers had a significant influence on the anxiety of pregnant women in receiving vaccines Covid-19.